Nitrogen Levels Regulate Sugar Metabolism and Transport in the Shoot Tips of Crabapple Plants - Zhang, Lihua; Sun, Simin; Liang, Yonghui; Li, Baiyun; Ma, Songya; Wang, Zhengyang; Ma, Baiquan; Li, Mingjun (Frontiers in Plant Science, 2021)
To comprehensively understand the responses of carbohydrate metabolism and transport to different levels of nitrogen supply in growing shoot tips of crabapple (Malus hupehensis Rehd), enzyme activities and related genes involved in the sugar metabolism pathway were investigated. The nitrogen and chlorophyll content of plants increased with increasing nitrogen supply. High nitrogen application increased the net photosynthesis rate and the growth rate of shoot tips but decreased the synthesis capability of sucrose and sorbitol in mature leaves. However, the shoot tips of plants under high-nitrogen treatment had higher contents of sucrose and sorbitol than did those under low-nitrogen treatment, while the activity of sucrose phosphate synthase and aldose-6-phosphate was increased and the transporters MdSOT and MdSUT were up-regulated. Moreover, the activities of enzymes involved in sucrose and hexose metabolism (including sucrose synthase, fructokinase, and hexokinase) were enhanced in the shoot tips of plants under high-nitrogen conditions, and the expression levels of MdSUSY3 and MdHK1 were significantly up-regulated. These findings indicate that a high nitrogen supply increases the metabolic capacity of assimilatory substances in shoot tips, accelerates the efficiency of sugar utilization and eventually leads to a rapid increase in the growth of shoot tips. Our results highlight that high nitrogen increases the capacity of sugar unloading and metabolic utilization in growing shoot tissues.